Beyond community forests: Carbon variability in Nepal’s mixed and pure private forests and its implications for climate policy - Dhakal, Sujana; Joshi, Rajeev; Subedi, Resham; Maraseni, Tek; Zhang, Han (Agriculture and Natural Resources, 2026)
Importance of the work: Private forests are a major component of Nepal’s landscape and have substantial potential for carbon sequestration, yet their role remains understudied and underutilized in national climate mitigation strategies, such as Reducing Emissions from Deforestation and Forest Degradation (REDD+). A comparative understanding of carbon stocks in different private forest management systems is crucial for developing effective policies and incentives. Objectives: To quantify and compare the above-ground biomass and carbon stocks in pure and mixed private forests, to analyze the structural attributes (diameter at breast height over bark (DBH), height, density) driving these differences and to identify species preferred by landowners to inform sustainable management and carbon policy. Materials and Methods: This study was conducted in the Rautahat District of Nepal’s Terai region. A systematic sampling design was applied, establishing 14 plots in a pure Eucalyptus camaldulensis Dehnh. forest and 4 plots in a mixed-species forest. Tree DBH, height and species were recorded in circular plots (each 250 m²). The above-ground biomass was calculated using a species-specific allometric equation and carbon stock was derived using a 0.47 conversion factor. A one-tailed t test was used to assess the significance of differences between forest types. Results: Pure eucalypt private forests in Nepal’s Terai stored 61% more carbon than mixed-species stands, offering a rapid climate mitigation pathway while balancing livelihood needs. Pure E. camaldulensis forests contained significantly higher mean ± SD carbon stocks (61.15 ± 0.78 t/ha) compared to mixed forests (37.87 ± 2.23 t/ha; p < 0.05). This carbon advantage was due to structural superiority as indicated by a larger tree height (16.11 m versus 10.43 m) and a higher stand density (695 trees/ha versus 560 trees/ha) than in pure stands. Beyond carbon, 11 tree species were identified as being managed by landowners primarily for timber, fuelwood and income generation, revealing private forests as socio-ecological systems where climate mitigation and livelihoods intersect. Main finding: Pure eucalypt private forests sequestered significantly more carbon per hectare than mixed species forests, demonstrating the high potential of the former for rapid carbon gains. This supports their integration into carbon incentive schemes, such as REDD+, while the diversity of species in mixed forests underscores the need for policies that balance carbon objectives with biodiversity and livelihood benefits. Private forests are no longer climate afterthoughts but strategic assets for Nepal’s mitigation targets.